The Effect of Bengkung Use on Abdominal Circumference Reduction in Postpartum Women - Fauziyah, Nailatul; Asiyah, Nor; Indrianingrum, Irawati (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: The postpartum period is a critical recovery period for mothers after childbirth and is prone to complications that contribute to high maternal mortality rates (MMR) in Indonesia. This study aims to evaluate the effect of bengkung use on reducing abdominal circumference in postpartum mothers as a non-pharmacological measure to support physical recovery after childbirth. Research Method: This study used a quasi-experimental design with a pre-test and post-test control group approach. The research subjects consisted of two groups: the experimental group, which used bengkung regularly, and the control group, which underwent early mobilization without the use of bengkung. Data collection was conducted by measuring the waist circumference both before and after the intervention. Results and Discussion: The study's results indicate that regular use of bengkung has a significant impact on reducing abdominal circumference in postpartum women. The effectiveness of bengkung in accelerating the process of uterine involution and abdominal muscle recovery is reinforced by the involvement of education and the comfort experienced by the mothers during use. Implications: These findings have a practical impact on midwifery services, particularly in integrating traditional practices that have been proven effective into standard postpartum care. Bengkung could be a safe, affordable, and locally based alternative intervention.